Effects of dendrobium polysaccharides on human brain microvascular endothelial cell injury induced by ox-LDL via regulating the miR-378 expression - Chen, Lai; Zhang, Shaohui; Liu, Xiaoying; Dai, Jiong; Yan, Zhenguo; Wu, Chunlan (Cellular and Molecular Biology, 2020)
Brain microvascular endothelial cells are a key part of the blood-brain barrier. This experiment was set up to investigate the effect and molecular mechanism of Dendrobium polysaccharide on oxidized low-density lipoprotein (ox-LDL)-induced damage to the human brain microvascular endothelial cells. For this purpose, human brain microvascular endothelial cells HBMEC were divided into control group (without any treatment), ox-LDL group (50 Î¼g/mL ox-LDL), Dendrobium polysaccharide low, medium and high concentration group (0.1 Î¼g/L, 0.2 Î¼g/L, 0.4 Î¼g/L Dendrobium polysaccharide+50 Î¼g/mL ox-LDL), ox-LDL+miR-NC group (transfection miR-378 mimic negative control+50 Î¼g/mL ox-LDL), ox-LDL+miR-378 group (transfected miR-378 mimics+50 Î¼g/mL ox-LDL), ox-LDL+DP+anti-miR-NC group (transfected miR-378 inhibitor negative control +0.4 Î¼g/L Dendrobium polysaccharide+50 Î¼g/mL ox-LDL), ox-LDL+DP+anti-miR-378 group (transfected miR-378 inhibitor+0.4 Î¼g/L Dendrobium polysaccharide+50 Î¼g/mL ox-LDL ). The kit was used to detect the levels of malondialdehyde (MDA) and the activities of superoxide dismutase (SOD) and catalase (CAT); flow cytometry to detect apoptosis; and Western blot to detect B-cell lymph tumor/leukemia-2 (Bcl-2) and Bcl-2 related X (Bax) protein expression; real-time fluorescence quantitative PCR (RT-qPCR) was used to detect the expression of miR-378. Results showed that after treatment with different concentrations of Dendrobium polysaccharides, MDA levels were decreased in ox-LDL-induced human brain microvascular endothelial cells, SOD and CAT activities were increased, apoptosis rate was decreased, Bcl-2 expression was increased, Bax expression was decreased, miR-378 expression was increased, in a dose-dependent manner (P<0.05). Overexpression of miR-378 inhibits ox-LDL-induced oxidative stress and apoptosis in human brain microvascular endothelial cells. Inhibition of miR-378 expression reversed the effect of Dendrobium polysaccharide on ox-LDL-induced damage to human brain microvascular endothelial cells. Then dendrobium polysaccharide may inhibit ox-LDL-induced oxidative stress and apoptosis in human brain microvascular endothelial cells by up-regulating the expression of miR-378.